Existence of a "Local" Co-operative Equilibrium in a Class of Voting Games - Kramer, Gerald H.; Klevorick, Alvin K. (Review of Economic Studies, 1974)
Gerald H. Kramer, Alvin K. Klevorick; Existence of a “Local” Co-operative Equilibrium in a Class of Voting Games12, The Review of Economic Studies, Volume